Crystalline structures in a one-dimensional two-component lattice gas with 1/r α interactions. (18th March 2016) - Levi, Emanuele; Minář, Jiří; Lesanovsky, Igor
Abstract: We investigate the ground state of a one-dimensional lattice system that hosts two different kinds of excitations (species) which interact with a power-law potential. Interactions are only present between excitations of the same kind and the interaction strength can be species-dependent. For the case in which only one excitation is permitted per site we derive a prescription for determining the ground state configuration as a function of the filling fractions of the two species. We show that depending on the filling fractions compatible or incompatible phases emerge. Furthermore, we discuss in detail the case in which one species is strongly and the other one weakly interacting. In this case the configuration of the strongly interacting (strong) species can be considered frozen and forms an effective inhomogeneous lattice for the other (weak) species. In this limit we work out in detail the microscopic ground state configuration and show that by varying the density of the weak species a series of compatible–incompatible transitions occurs. Finally, we determine the stability regions of the weak species in the compatible phase and compare it with numerical simulations.